Direct identification of edible insects by MALDI-TOF mass spectrometry. (June 2017) - Ulrich, Sebastian; Kühn, Ulrike; Biermaier, Barbara; Piacenza, Nicolo; Schwaiger, Karin; Gottschalk, Christoph; Gareis, Manfred
Abstract: The consumption of edible insects (entomophagy) will gain greater significance facing the increasing global population, which is suggested to reach 9 billion people in 2050 (FAO., 2009). Due to their high amount of proteins, fatty acids, vitamins, and minerals insects represent a valuable source of essential nutrients. While the consumption of insects is very common in many countries of Africa and Asia, there is a far smaller acceptance for entomophagy in Western cultures. Though, products such as noodles or burger paddies made from insect meal have a better compliance and can already be purchased in some countries of the European Union. This processing step however involves the risk of adulteration, because there is no more possibility to authenticate the insects once they are ground. The aim of this study was to investigate whether edible insects could be measured and distinguished by MALDI-TOF MS (matrix-assisted laser desorption ionization-time of flight mass spectrometry). Therefore, different kinds of edible insects (buffalo worms, mealworms, crickets and grasshoppers) were purchased via online shops and ground subsequently. The insect powder was extracted by vigorously shaking in diluted formic acid and measured by MALDI-TOF MS. The measurement provided reproducible as well as specific mass spectra and enabled a precise differentiation of the different species.